The Effect of The NHT (Numberead Heads Together) Learning Model on the Activity and Learning Outcomes of Science Students in MIN Sihaborgoan Dalan - Maya Sari Harahap; Ismira Ismira; Siti Aisyah (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This article aims to determine the effect of the NHT (Numberread Heads Together) learning model on student activity and science learning outcomes at MIN Sihaborgoan Dalan. This study employed a quasi-experimental design with a non-equivalent control group. The population and sample were 20 fourth-grade students at MIN Sihaborgoan Dalan. The instruments used in this study were tests and observation sheets. Data analysis techniques used were descriptive tests (mean, median, mode, and standard deviation) and inferential tests (normality, t-test, and MANOVA). Based on data analysis using SPSS 20, the normality test for problem-solving ability and learning outcomes using multivariate tests showed a sig > 0.05 for the pretest and posttest of the experimental class. The normality test using the based mean showed a sig > 0.05 for the pretest and posttest of the experimental class. The MANOVA test showed a significance value of 0.000. 0.000 < 0.05 then ???????? is rejected and ???????? is accepted. Based on this, it can be concluded that there is an influence of the NHT (Numberread Heads Together) Learning Model on the activeness and learning outcomes of science students on plant propagation material in class IV MIN Sihaborgoan Dalan.